Attack Graph-Based Approach For Enterprise Networks Security Analysis (International Journal of Engineering and Computer Science, 2017)
Network administrators are always faced with numerous challenges of identifying threats and in retrospect, securing the organization’s network. The classical approach of identifying the vulnerability in the network is by using commercially developed tools that do not take into cognisance vulnerability interaction between network elements and their behavioral pattern.Therefore, network administrators have to take a hollistic methods to identify vulnerability interrelationships to be captured by an attack graph which will help in identifying all possible ways an attacker would have access to critical resources. The objective therefore is to design an attack graph–based approach for analyzing security vulnerabilities in enterprise networks, implement and evaluate performance of the approach.